Sarcocystis sinensis in slaughtered cattle from Central of Iran - Hajimohammadi, B; Eslami, G; Manafi, L; Athari, SS; Boozhmehrani, MJ (Journal of the Hellenic Veterinary Medical Society, 2022)
Sarcocystis is a food borne parasite as an intracellular parasite with two-host life cycle. Humans serve as either intermediate or definitive hosts among different species. Sarcocystosis is a very important disease because of its widespread prevalence with an impact on production and animal health. We aimed to assess S. sinensis in cattle from the desert area of Iran, using conventional PCR, targeting 18S rRNA. Also, the phylogenic analysis was done to mention isolate and the related ones in Genbank. From the 108 beef samples of heart, esophagus, intercostal muscle, diaphragm, and tongue harboring Sarcocystis spp. stored in the BioBank of the Research Center for Health and Food Safety, Shahid Sadoughi University of Medical Sciences, Yazd, Iran, DNA extraction was done. Amplification was done using the primer pair of SAR-F: 5’-TGGCTAATACATGCGCAAATA-3’ and SAR-R: 5’-AACTTGAATGATCTATCGCCA-3’ For the target of 18S rRNA gene. Sequencing was done. The interesting sequence was edited and then analyzed with BLAST. Then, multiple alignments were conducted using T-coffee. The mentioned sequence was submitted to GenBank in NCBI. Evolutionary analyses were conducted in MEGA7. In order to statistical analysis of the presence of Sarcocystis sinensis significantly with sex, age, and location, the Fisher’s Exact test was done using SPSS 16.0 (SPSS Inc. Chicago, USA). The p-value < 0.05 was considered significant. Out of 108 samples, five isolates were identified as S. sinensis. The distribution of S. sinensis was related to age (p<0.05) but had no significant difference with gender (p>0.05). Phylogenic analysis showed a similarity of S. sinensis with S. hominis. From a food safety viewpoint, this study employed a molecular approach to identify S. sinensisin in cattle meat. To the best of our knowledge, this is the first report of S. sinensis in the desert area from Iran.